IMPLEMENTASI ZAKAT PERTANIAN DI DESA PUTER KECAMATAN KEMBANGBAHU KABUPATEN LAMONGAN - Bela, Nabela Agustin; Marlina Ekawaty (Islamic Economics and finance in Focus, 2024)
This research was conducted to determine the implementation of agricultural zakat in Puter village, Kembangbahu District, Lamongan Regency. The aim of this research is to expand farmers' knowledge about agricultural zakat. The research method used is qualitative research by collecting data through observation and interviews with farmers, both owners and tenants in Puter village. The results of this research indicate that the knowledge of farmers in Puter Village about agricultural zakat is still low and the implementation of agricultural zakat has not been carried out.